Facilitating knowledge sharing and reuse in information service using information retrieval technique - Sugunnasil P. (2017)
© 2016 ACM. Information service is an important assistive tool in the knowledge sharing process. The knowledge sharing process covers a wide range of operations ranging from a course registration process to flight ticket buying. A good service could help both the service providers and the service users. The service users could get the right information at the right time and at the right place; whereas the service providers could reduce the amount of work created by uninformed users. In this paper, an electronic service framework (e-service) is proposed to assist the information service. This framework is based on an information retrieval technique to discover information. As a result, the information can be accessed at any place and any time. Furthermore, the issue of information quality is also a part of this framework. Each piece of information will be provided with tags and a weight. The tags will be used for categorization while the weight will be used to determine the quality of the information. Ultimately, the information will be evaluated by the users whose comments and scores will later be used to improve the system.